BK polyomavirus-associated nephropathy in kidney transplant - Méndez Chacón, Pedro (2015)
Two documented cases of BK polyomavirus-associated nephropathy (BKVN) seen at Hospital Edgardo Rebagliati Martins, EsSalud, Lima, Peru are reported. Final BKVN diagnosis was confirmed by renal biopsy and electron microscopy study. Case 1: Renal functional deterioration was not controlled despite reduction of immunosuppression and addition of antiviral drugs (leflunomide and ciprofloxacin), evolving to renal failure and subsequent kidney retransplantation. Case 2: The therapeutical management consisted in intravenous immunoglobulin infusion linked to reduction of immunosuppression; this resulted in modest histological improvement and stabilization of renal function. Both renal grafts concomitantly presented BKVN and histological lesions consistent with acute rejection, pending interpretation. In conclusion presence of BK polyomavirus is a serious problem for transplanted kidneys. The best treatment is based on early diagnosis and subsequent reduction of immunosuppression. It is essential to have an appropriate methodology for precise diagnosis. Early electron microscopy is a valuable method for viral etiologic diagnosis. Retransplantation is considered a treatment option when faced with possible BKVN-related graft loss (Case 1).